Leadership And Motivation To Built Morale And Quality Of Lecturer's Work - Azis Rachman (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The four variables presented in this article examine leadership styles, motivation, work spirit, and quality of work for lecturers and teaching staff at private universities in Gorontalo province. This research is an experimental type, where is presented is the result of the analysis and relationship between every variable. The data analysis tool is carried out using the Smart PLS (Partial Least Squares) application. Where the results of this study indicate that leadership style does not directly affect the quality of work. Motivation has a positive and significant effect on work morale. Morale has a positive and significant effect on the quality of work and motivation has a positive and significant effect on the quality of work.